2017
DOI: 10.1017/s0025315417001825
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategy of Brachidontes rodriguezii (Bivalvia: Mytiloida) in the South-western Atlantic Ocean

Abstract: This study consisted in the characterization of reproductive aspects such as oocytes morphology, temporal variation in size and frequency of oocytes and the reproductive cycle of the mussel Brachidontes rodriguezii. This species dominates the rocky intertidal coast of Buenos Aires province, Argentine and is a prey item of several exploited species; however, due to the introduction of piers and seawalls, as a consequence of anthropogenic activities, the species also inhabits sandy coasts. Mussels were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In terms of the size of oocytes, the mean area of previtellogenic oocytes did not differ during the study period, mean size was around 130 mµ 2 and previous results in Villa Gesell showed similar values with mean areas ranging between 30-400 mµ 2 , reaching in October 2012 the highest mean value of the entire period (260.92 mµ 2 ) (Torroglosa & Giménez, 2019a). The same for the early vitellogenic oocytes showed a significant increased in size reaching maximum values in austral winter (~550 mµ 2 ), while in the lower level, early vitellogenic oocytes reached the highest mean value of the entire period (691.16 mµ 2 ) by November 2012 in austral spring (Torroglosa & Giménez, 2019a). Finally, for the vitellogenic oocytes, in this study record an increase in oocyte size reaching the maximum mean value 1354.70 mµ 2 by October 2012 while in the lower level vitellogenic oocytes area reached the highest mean value (1623.63 mµ 2 ) by December 2011 (Torroglosa & Giménez, 2019a).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In terms of the size of oocytes, the mean area of previtellogenic oocytes did not differ during the study period, mean size was around 130 mµ 2 and previous results in Villa Gesell showed similar values with mean areas ranging between 30-400 mµ 2 , reaching in October 2012 the highest mean value of the entire period (260.92 mµ 2 ) (Torroglosa & Giménez, 2019a). The same for the early vitellogenic oocytes showed a significant increased in size reaching maximum values in austral winter (~550 mµ 2 ), while in the lower level, early vitellogenic oocytes reached the highest mean value of the entire period (691.16 mµ 2 ) by November 2012 in austral spring (Torroglosa & Giménez, 2019a). Finally, for the vitellogenic oocytes, in this study record an increase in oocyte size reaching the maximum mean value 1354.70 mµ 2 by October 2012 while in the lower level vitellogenic oocytes area reached the highest mean value (1623.63 mµ 2 ) by December 2011 (Torroglosa & Giménez, 2019a).…”
Section: Discussionsupporting
confidence: 70%
“…The stress conditions increase in the higher intertidal zone as consequence of tides, organisms spend less time feeding and the longer exposure to aerial conditions leads to desiccation (Petes et al 2008;Helmuth et al 2011). Previous studies carried out in the same area revealed some reproductive features of B. rodriguezii in the low intertidal (Torroglosa & Giménez, 2019a) and a differential growth probably due to tides (Torroglosa & Giménez, 2019b).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Different reproductive patterns were found here on B. rodriguezii's females from the two tidal levels studied. According to Torroglosa and Giménez (2019b), once adulthood is achieved individuals are at least potentially capable of spawning year-round. However, females at long air exposure (having more energy density, but less energy condition index) showed only one marked spawning episode in Summer at highest sea water temperature, while those of the lower level presented two more pronounced spawning events, in Spring and Autumn.…”
Section: Discussionmentioning
confidence: 99%